2011
DOI: 10.1258/acb.2010.010219
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of high sensitivity and contemporary troponin assays for the early detection of acute myocardial infarction in the emergency department

Abstract: Background: Current guidelines define acute myocardial infarction (AMI) by the rise and/or fall of cardiac troponin with !1 value above the 99th percentile. Past troponin assays have been unreliable at the lower end of the range. Highly sensitive assays have therefore been developed to increase the clinical sensitivity for detection of myocardial injury. hsTnT was superior to TnT (P , 0.001/0.013 at baseline/follow-up) but equivalent to TnI 3. For patients with a final diagnosis of AMI, baseline troponins were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
65
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 25 publications
(71 reference statements)
4
65
0
Order By: Relevance
“…Aldous et al examined the introduction of the suggested time-dependent delta-change criterium for the diagnosis of acute MI in the ED (49): Introduction of the diagnostic criterium that a time-dependent increase (or fall) of hs-cTn )50% is necessary to diagnose acute MI increase specificity )95% at the cost of sensitivity (hs-cTnT: 61.8%; hs-cTnI: 68.2%). These findings support the notion that diagnostic reasoning in emergency medicine cannot be reduced to pure mathematical calculations of biomarker concentrations (49,50). Diagnostic reasoning and deduced therapeutic management strategies can only be made correctly, when all available information about the patient is used.…”
Section: Time-dependent Changes Of Troponin Levels In Acute Myocardiasupporting
confidence: 73%
“…Aldous et al examined the introduction of the suggested time-dependent delta-change criterium for the diagnosis of acute MI in the ED (49): Introduction of the diagnostic criterium that a time-dependent increase (or fall) of hs-cTn )50% is necessary to diagnose acute MI increase specificity )95% at the cost of sensitivity (hs-cTnT: 61.8%; hs-cTnI: 68.2%). These findings support the notion that diagnostic reasoning in emergency medicine cannot be reduced to pure mathematical calculations of biomarker concentrations (49,50). Diagnostic reasoning and deduced therapeutic management strategies can only be made correctly, when all available information about the patient is used.…”
Section: Time-dependent Changes Of Troponin Levels In Acute Myocardiasupporting
confidence: 73%
“…These assays shorten the time to diagnosis by 3 h compared to the use of conventional troponin assays with blood sampling at admission and after 3 and 6 h (2, 3 ). On the other hand, high-sensitivity troponin assays also increase the number of patients presenting with increases in troponin from other causes than MI (4,5 ). Such increases are particularly common in elderly patients (6 ), and lead to reductions in the diagnostic specificity of troponin results.…”
mentioning
confidence: 99%
“…Because physician-based subjective calculation of post-test probabilities for an individual patient is prone to errors, 3 diagnostic reasoning in patients with acute coronary syndrome should include formal risk assessment using validated risk assessment tools such as GRACE, TIMI or PURSUIT risk scores. 4 Moreover, the aim of disposition decisions in the ED is not to identify patients with acute MI or risk of death alone, but to identify patients at increased risk for…”
Section: High-sensitivity Troponin Assays and Clinical Decisionsmentioning
confidence: 99%